2007
DOI: 10.1177/0306624x07307352
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities and Delinquency

Abstract: Research consistently illustrates that several intellectual disabilities--namely, learning disabilities (LD), low intelligence, challenging behavior, and inadequate adaptive behavior, as well as attention deficit hyperactivity disorder (ADHD)--are considered risk factors for antisocial and criminal behavior. Although much attention has been paid to the relationship of LD, ADHD, and criminal behavior, three research topics have been overlooked: the frequency of LD with ADHD among inmates, the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 44 publications
0
21
0
4
Order By: Relevance
“…On the other pole Einat and Einat (2008) reported high rates of LD (69.6%) among a random sample of 89 Israeli inmates. In addition, significant relationships were found between LD, number of years of education and the age of the onset of criminal activity [75]. In another example, it was found that LD were overrepresented among a sample of homeless adults (N = 133) [76].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other pole Einat and Einat (2008) reported high rates of LD (69.6%) among a random sample of 89 Israeli inmates. In addition, significant relationships were found between LD, number of years of education and the age of the onset of criminal activity [75]. In another example, it was found that LD were overrepresented among a sample of homeless adults (N = 133) [76].…”
Section: Resultsmentioning
confidence: 96%
“…Three articles [75][77] (4.83%) were classified into this domain and described extremely different results concerning adults with LD. On one pole, Seo, Abbott, and Hawkins (2008) compared adults with and without LD (N = 571) and found no significant differences between the groups at age 24 in the areas of schooling, employment, income, receipt of public aid and involvement in crime [77].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated a high prevalence of psychiatric diagnoses such as conduct disorder (CD), antisocial personality disorder (ASPD), substance use disorder (SUD), ADHD and learning disorder among mainly male prison inmates (2628), and one recent study showed that approximately 50% of male inmates have current ADHD and related problems (29). At the time of the present investigation there were no studies dedicated specifically to female convicts.…”
Section: Introductionmentioning
confidence: 99%
“…Estos estudios ofrecen una prevalencia del trastorno en prisión que abarca un rango amplio, de un 10 hasta un 70% (Ghanizadeh, Mohammadi, Akhondzadeh, & Sanaei-Zadeh, 2011). Asimismo, se observa que la presencia del TDAH aparece frecuentemente asociado a otros trastornos, actuando como factor de riesgo para la conducta criminal y antisocial, además de predecir el futuro consumo de sustancias (Einat & Einat, 2008;Ghanizadeh et al, 2011;Rösler et al, 2004).…”
unclassified
“…Asimismo, estos resultados confi rman una presencia del TDAH en prisión más elevada que en población general (Einat & Einat, 2008;Ghanizadeh et al, 2011;Rösler et al, 2004), destacando en la población reclusa con TDAH un control de impulsos bajo y un riesgo de reincidencia elevado entre los internos (Eme, 2008), la cual se incrementa hasta cinco veces más si el preso ha cumplido condena en más de una ocasión (Vicens-Pons & Grupo PRECA, 2009). En esta línea, el estudio de Sanz-García et al (2010), realizado con internos en tratamiento psiquiátrico en el medio penitenciario, refi ere que aquellos con TDAH delinquen a más temprana edad, con una media de comisión del primer delito a los 22 años frente a los 29 años del resto de reclusos con otras patologías psiquiátricas.…”
unclassified